Робототехника в процессе обучения - Konradi T. A. (Инновационные технологии в науке и образовании, 2015)
Robotics has been widely used in medicine, aerospace, manufacturing, film and much more. At this point in time, robotics as an academic discipline in educational institutions is in the nature of additional education, but in some regions of our country want to introduce robotics as a separate, mandatory for learning discipline. At the present time it is not carried out specific research on the use of robotics in the learning process.
Keywords: образовательный процесс; дополнительное образование; исследования; робототехника; элективные курсы; педагогические цели; робототехнический набор; компоненты учебного процесса; урочные формы работы; проектная работа; robotics; robotic kit; additional education; educational process; pedagogical objectives; the components of the educational process; a portion to form the work; elective courses; club and sectarian forms of work; research; project work; клубная форма работы; кружковая форма работы